1975
DOI: 10.1002/cpt1975172134
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic potency of N‐acetylprocainamide

Abstract: Compared to procainamide in an animal arrhythmic model, the antiarrhythmic potency of the N-acetylated metabolite of procainamide (NAPA) was 92% with respect to dose and 70% with respect to plasma level. The antiarrhythmic effects of combinations of the drugs were additive. Measurements of procainamide and NAPA plasma levels needed to suppress ventricular extrasystoles suggested that both compounds are nearly equipotent in patients as well. The average plasma level required for arrhythmia control in these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(42 citation statements)
references
References 2 publications
(2 reference statements)
0
42
0
Order By: Relevance
“…A similar relationship between the occurrence of systemic lupus erythematosus and slow acetylation phenotype has been reported for patients receiving procainamide (Henningsen, Cederberg, Hanson & Johansson, 1975). In addition, it has been suggested that the N-acetylprocainamide may make a significant contribution to the antiarrhythmic effect resulting from procainamide administration (Elson, Strong, Lee & Atkinson, 1975). Isoniazide-related hepatic injury is associated with rapid drug acetylation and probably hepatotoxicity of the drug metabolites (Mitchell, Zimmerman, Ishak, Thorgeirsson, Timbrell, Snodgrass & Nelson, 1976).…”
Section: Discussionmentioning
confidence: 57%
“…A similar relationship between the occurrence of systemic lupus erythematosus and slow acetylation phenotype has been reported for patients receiving procainamide (Henningsen, Cederberg, Hanson & Johansson, 1975). In addition, it has been suggested that the N-acetylprocainamide may make a significant contribution to the antiarrhythmic effect resulting from procainamide administration (Elson, Strong, Lee & Atkinson, 1975). Isoniazide-related hepatic injury is associated with rapid drug acetylation and probably hepatotoxicity of the drug metabolites (Mitchell, Zimmerman, Ishak, Thorgeirsson, Timbrell, Snodgrass & Nelson, 1976).…”
Section: Discussionmentioning
confidence: 57%
“…From clinical and pharmacological considerations, KochWeser (1971) has advocated that procainamide should be administered in three hourly doses. However, Biggar (1972) reports satisfactory control of arrhythmias with six hourly administration, perhaps due to anti-arrhythmic effect of the major metabolite -N acetylprocainamide -which has a substantially longer half-time in the plasma than the parent compound (Elson, Strong, Lee & Atkinson, 1975). In the present study three hourly administration was the exception (12%) rather than the rule: the most frequent pattern of administration being 4-5 times daily (40% of recipients).…”
Section: Methodsmentioning
confidence: 40%
“…NAPA, the principal metabolite of procainamide in man,9 may not have this toxicity and may become an alternative drug inasmuch as it has antiarrhythmic activity in both animal models4 9, 10 and in patients. 4 Our canine electrophysiologic comparative study of procainamide and NAPA may be useful to compare their cardiac effects and to delineate the possible mechanism of action of NAPA.…”
Section: Discussionmentioning
confidence: 99%